(untitled) (Journal of Face Aesthetics, 2024)
In the 21st century, a very important element of interpersonal contacts is the perception of another person. Appearance became the essence of these relationships. It is not only the clothes, but the physiognomy of the person we are in contact with. Aesthetic medicine treatments are most often used by women, but in the last decade this has changed, because men have also started to take care of the appearance of their face. That is why it is so important to address the topic of treatments that gentlemen undergo.